1990
DOI: 10.1037/0021-9010.75.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Coping, negative affectivity, and the work environment: Additive and interactive predictors of mental health.

Abstract: The present study tested the hypothesis that direct coping would moderate relations between work stress and mental health outcome, whereas suppression (a form of emotion-focused coping) would show an overall effect on outcome. Data on coping, perceived work demand and support, and affective symptoms were obtained from trainee teachers (N = 157). The results supported the hypothesis. Gender differences also were observed; men reported more use of suppression than did women. In addition, negative affectivity (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
245
2
18

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(281 citation statements)
references
References 87 publications
16
245
2
18
Order By: Relevance
“…Entretanto, dada a importância da dimensão situacional na própria defi nição de coping, medidas desenvolvidas para situações específi cas são sempre bem vindas por apresentarem estratégias que realmente se aplicam ao contexto em questão. Em reforço a este argumento, Parkes (1990) ressalta que algumas estratégias de coping que são consideradas efetivas em ambiente doméstico e no relacionamento conjugal não têm se mostrado capazes de aliviar o estresse no contexto ocupacional, ou conseguem fazê-lo apenas em uma extensão limitada. Uma possível razão para este fato é que as limitações inerentes ao contexto ocupacional restringem as possibilidades para a ação efetiva dos indivíduos, que passam a depender de diferentes estratégias de coping.…”
Section: F a Pinheiro And Colsunclassified
See 3 more Smart Citations
“…Entretanto, dada a importância da dimensão situacional na própria defi nição de coping, medidas desenvolvidas para situações específi cas são sempre bem vindas por apresentarem estratégias que realmente se aplicam ao contexto em questão. Em reforço a este argumento, Parkes (1990) ressalta que algumas estratégias de coping que são consideradas efetivas em ambiente doméstico e no relacionamento conjugal não têm se mostrado capazes de aliviar o estresse no contexto ocupacional, ou conseguem fazê-lo apenas em uma extensão limitada. Uma possível razão para este fato é que as limitações inerentes ao contexto ocupacional restringem as possibilidades para a ação efetiva dos indivíduos, que passam a depender de diferentes estratégias de coping.…”
Section: F a Pinheiro And Colsunclassified
“…Coping tem mostrado relações signifi cativas com variáveis demográfi cas como gênero (Parkes, 1990), medidas de diferenças individuais como locus de controle (Parkes, 1984), neuroticismo e depressão (Endler & Parker, 1990), afetividade negativa (Parkes, 1990) e saúde (Cohen, 1987). Folkman e Lazarus (1980) Relações interativas entre coping, estressores no trabalho e efeitos sobre a saúde e o desempenho nas organizações também têm sido relatadas (Parkes, 1986(Parkes, , 1990(Parkes, e 1994.…”
Section: F a Pinheiro And Colsunclassified
See 2 more Smart Citations
“…Watson and Pennebaker (1989) found that NA was significantly related to self-reports of physical complaints, however it did not appear to be related to long-term health problems. Similarly, NA has been found to be negatively related to coping resources (Parkes, 1990). Perhaps because of its seemingly pervasive nature, NA has been claimed as a nuisance variable in stress research (Brief et al, 1988;Elliott, Chartrand, & Harkins, 1994).…”
Section: Stress Strain Coping Positive and Negative Affectivitymentioning
confidence: 99%